2018
DOI: 10.3390/app8091582
|View full text |Cite
|
Sign up to set email alerts
|

Robust Design of 3D-Printed 6–18 GHz Double-Ridged TEM Horn Antenna

Abstract: A robust design of a 3D-printed 6–18 GHz double-ridged TEM horn antenna is proposed in this paper. The designed TEM horn antenna has two parts: an adaptor and a horn aperture. The adaptor is realized using a double-ridged waveguide to extend the operating bandwidth of the dominant mode (TE10 mode). Meanwhile, the horn aperture section is implemented in an exponentially tapered configuration to match the impedance of the double-ridged waveguide with the intrinsic impedance. The performance of the initially desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Although FDM is capable of printing various filament polymers, acrylonitrile butadiene styrene (ABS), and polylactic acid (PLA) are the most commonly used polymers for DRHA printing. [4][5][6][7][8][9] Despite this, there is still a shortage of new literature or reports related to the application of 3D printing in DRHA, and most of them were published within the past 8 years. [4][5][6][7][8][9][10][11][12][13] The comparative characteristics of the study of 3Dprinted DRHA with previous works are listed in Table 1.…”
Section: Brief Review Of 3d-printed Drhamentioning
confidence: 99%
“…Although FDM is capable of printing various filament polymers, acrylonitrile butadiene styrene (ABS), and polylactic acid (PLA) are the most commonly used polymers for DRHA printing. [4][5][6][7][8][9] Despite this, there is still a shortage of new literature or reports related to the application of 3D printing in DRHA, and most of them were published within the past 8 years. [4][5][6][7][8][9][10][11][12][13] The comparative characteristics of the study of 3Dprinted DRHA with previous works are listed in Table 1.…”
Section: Brief Review Of 3d-printed Drhamentioning
confidence: 99%
“…The high computational cost of such procedures-a result of massive EM analyses required by both local [22] and global [23] search routines, is a serious practical problem. It is even more pronounced for uncertainty quantification procedures, especially robust (tolerance-aware) design [24], [25].…”
Section: And Implementation Of Variousmentioning
confidence: 99%
“…In another study, the gains of horn antennas, which are implemented on a 3D printer using ABS filament, are experimentally investigated for the cases where they are coated with copper, chrome and nickel (Genç et al, 2017). On the other hand, a double-backed horn antenna was implemented in (Lee et al, 2018) to operate in the 6-18 GHz range, printed on a 3D printer, and its performance was measured after coating it with silver-containing conductive paint. It has been shown that this antenna also works as expected.…”
Section: Introductionmentioning
confidence: 99%